High‐wire act: the poised genome and cellular memory. (21st December 2014) - Puri, Deepika; Gala, Hardik; Mishra, Rakesh; Dhawan, Jyotsna
<x xml:space="preserve">Abstract</x> Emerging evidence aided by genome‐wide analysis of chromatin and transcriptional states has shed light on the mechanisms by which stem cells achieve cellular memory. The epigenetic and transcriptional plasticity governing stem cell behavior is highlighted by the identification of 'poised' genes, which permit cells to maintain readiness to undertake alternate developmental fates. This review focuses on two crucial mechanisms of gene poising: bivalent chromatin marks and RNA polymerase II stalling. We provide the context for these mechanisms by exploring the current consensus on the regulation of chromatin states, especially in quiescent adult stem cells, where poised genes are critical for recapitulating developmental choices, leading to regenerative function.